(untitled) (Journal of International Studies, 2017)
Conflict recurrence in the eastern Democratic Republic of Congo (DRC) provides a litmus test to the Southern African Development Community’s (SADC’s) capacity to sustainably resolve the conflict and build peace. The surrender of the March 23 (M23) rebels, followed by overtures to incorporate the same into the Congolese military and political institutions, seem not to have made much significant impact on the security stability in the eastern part of the country. Armed activities by militia groups such as the Democratic Liberation Forces of Rwanda (FDLR), the Allied Democratic Forces (ADF), the Lord’s Resistance Army (LRA), and various Mayi Mayi groups are likely to cause a recurrence of a fully fledged armed conflict in eastern Congo. Whilst the UN Mission for the Stabilisation of Congo (MONUSCO), along with its Intervention Brigade continue to make efforts to support the Congolese government to address the security situation in the country, this article presents a critical analysis on the prospects and constraints of SADC to sustainably resolve the conflict and build peace in the context of conflict recurrence. For purposes of conflict resolution and peacebuilding, the DRC falls within SADC’s area of sub-regional responsibility, which overlaps that of the International Conference of the Great Lakes Region (ICGLR). The paper looks at the political/diplomatic and military/ security initiatives that SADC can take to complement the current efforts of critical role players such as MONUSCO and ICGLR in sustainably resolving the recurring conflict and building peace.It also analyses the prospects of such sub-regional initiatives. Considering the conflict matrix of the eastern Congo conflict with specific reference to its recurrence, an examination of the likely constraints that SADC could encounter in trying to resolve the eastern Congo conflict will be presented. Policy suggestions will be proffered on what can be done to encounter such constraints.The research adopted a qualitative approach premised on interviews. Secondary sources, including key policy documents and statements of the SADC, AU, ICGLR and UN, were utilised. To complement the primary sources, structured opportunity interviews were conducted at seminars and workshops with academics and senior political and security analysts conversant with the SADC conflict and peace dynamics.